Transfer of antibiotic-resistant bacteria via ballast water with a special focus on multiple antibiotic-resistant bacteria: A survey from an inland port in the Yangtze River. (May 2021) - Lv, Baoyi; Jiang, Ting; Wei, Huawei; Tian, Wen; Han, Yangchun; Chen, Lisu; Zhang, Di; Cui, Yuxue
Abstract: Ship ballast water can transfer harmful organisms, including antibiotic-resistant bacteria (ARB), among geographically isolated waters. In this study, the presence and composition of ARB and multiple ARB (MARB) were investigated in the ballast waters of 30 vessels sailing to the Port of Jiangyin (Jiangsu Province, China). ARB were detected in 83.3% of the ship's ballast water samples. Moreover, penicillin- and cephalothin-resistant bacteria were the most and least prevalent ARB in the ballast waters, respectively. Oxytetracycline-, chloramphenicol-, tetracycline-, and vancomycin-resistant bacteria were also detected at high concentrations. The multiple antibiotic resistance index demonstrated the presence of MARB, which exceeded 200% in the ballast waters of five ships. Furthermore, 15 species, including the human opportunistic pathogens Vibrio alginolyticus and Serratia nematodiphila, were resistant to at least three antibiotics. Therefore, the potential ecological risk of ARB warrants further attention because of their effective invasion by ballast water. Graphical abstract: Unlabelled Image Highlights: Antibiotic-resistant bacteria could be found in 83.3% of ship's ballast water samples. The sum of antibiotic-resistant bacteria was ranged from 14 to 9.0 × 10 3  CFU/mL in ballast waters. Fifteen species of multiple antibiotic-resistant bacteria were isolated from ship ballast waters. Pathogenic multiple antibiotic-resistant bacteria were detected in ballast waters.